Hydraulic conductivities of fractures and matrix in Slovenian carbonate aquifers - Timotej Verbovšek (Geologija, 2008)
Hydraulic conductivities and specific storage coefficients of fractures and matrix in Slovenian carbonate aquifers were determined by Barker’s method for pumping test analysis, based on fractional flow dimension. Values are presented for limestones and mainly for dolomites, and additionally for separate aquifers, divided by age andlithology in several groups. Data was obtained from hydrogeological reports for 397 water wells, and among these, 79 pumping tests were reinterpreted. Hydraulic conductivities of fractures are higher than the hydraulic conductivities of matrix, and the differences are highly statistically significant. Likewise, differences are significant for specific storage, and the values of these coefficients are higher in the matrix. Values of all coefficients vary in separate aquifers, and the differences can be explained by diagenetic effects, crystal size, degree of fracturing, andcarbonate purity. Comparison of the methods, used in the reports, and the Barker’s method (being more suitable for karstic and fractured aquifers), shows that the latter fits real data better.